How Latin America Fell Behind 1997
DOI: 10.1515/9781503622500-013
|View full text |Cite
|
Sign up to set email alerts
|

10. Factor Endowments, Institutions, and Differential Paths of Growth Among New World Economies: A View from Economic Historians of the United States

Abstract: for helpful discussions and •omments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 511 publications
(68 citation statements)
references
References 7 publications
1
62
0
5
Order By: Relevance
“…This paper contributes to a large literature on the role of agriculture in economic development (e.g., Johnston and Mellor, 1961;Gollin, 2010). In particular, we add to a strand of this literature that studies the effects of specialization in particular products as a result of their distinctive features, e.g., returns to scale, seasonality or labor intensity (Engerman and Sokoloff, 1997;Sokoloff and Dollar, 1997;Eberhardt and Vollrath, 2016). We rekindle the staple theory of economic growth (Innis, 1930(Innis, , 1940 and the theory of linkages (Hirschman, 1958), examining various ways in which primary products can shape the process of growth and structural change.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This paper contributes to a large literature on the role of agriculture in economic development (e.g., Johnston and Mellor, 1961;Gollin, 2010). In particular, we add to a strand of this literature that studies the effects of specialization in particular products as a result of their distinctive features, e.g., returns to scale, seasonality or labor intensity (Engerman and Sokoloff, 1997;Sokoloff and Dollar, 1997;Eberhardt and Vollrath, 2016). We rekindle the staple theory of economic growth (Innis, 1930(Innis, , 1940 and the theory of linkages (Hirschman, 1958), examining various ways in which primary products can shape the process of growth and structural change.…”
Section: Introductionmentioning
confidence: 92%
“…Other work has shown that agricultural production patterns can influence institutions and culture. In their influential work on compartive development in the Americas, Engerman and Sokoloff (1997) and Engerman and Sokoloff (2002) argue that scale economies in the production of cotton, sugar, rice, tobacco, and coffee induced slave plantations and generated inequalities that became embodied in institutions, ultimately harming long-run performance (see also Nunn, 2008;Bruhn and Gallego, 2012). In a recent study with Chinese data, Talhelm et al (2014) argue that rice production fosters collectivistic cultures, whereas wheat production is more conducive to individualism.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The word "reversal of fortune" refers to a significant period in which some of the world's most powerful civilizations in the old period sacrifice their correlative educational control to areas that may not have previously held well-developed communities but now encourage the world's most powerful states in terms of total GDP (Acemoglu, Johnson & Robinson, 2001, 2002Engerman & Sokoloff, 1997, 2005a, 2005bNunn, 2008aNunn, , 2008b 1 . However, both sociologists and financial scholars have recorded this template of global withdrawal in general economic fortunes over time, actual studies for such a transition can be found in the indirect effect among factors of wealth in 1500 (urbanization relationship between population frequency) and factors of the existing level of wealth.…”
Section: Reversal Of Fortunementioning
confidence: 99%
“…The quantitative study of colonialinstitutional reasons of variation in development patterns in the AJR thesis is unique. Angeles (2007), Bairoch (1993, Banerjee and Iyer (2005), Bertocchi and Canova (2002), Engerman & Sokoloff (1997, 2005a, 2005b, Jones (2016aJones ( , 2016b, Nunn (2008aNunn ( , 2008b, are a few examples of papers that have attempted to link post-colonial findings to (1995). We will analyze the causal pathways that have emerged from the AJR study first, and then broaden the AJR thesis to include additional potential aspects to improve our knowledge of complicated historical events.…”
Section: Reversal Of Fortune In Context Of Orgazinational Perspective...mentioning
confidence: 99%
See 1 more Smart Citation